2009
DOI: 10.1111/j.1095-8649.2009.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent growth rate in an age‐structured population: a field study on stream‐dwelling brown troutSalmo trutta

Abstract: A field experiment during autumn, winter and spring was performed in a small stream on the west coast of Sweden, aiming to examine the direct and indirect consequences of density-dependent intercohort competition in brown trout Salmo trutta. Individual growth rate, recapture rate and site fidelity were used as response variables in the young-of-the-year (YOY) age class, experiencing two different treatments: presence or absence of yearlings and over-yearlings (age > or = 1+ year individuals). YOY individuals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 101 publications
(150 reference statements)
4
50
2
Order By: Relevance
“…Growth rates in the subyearling age class were overall negatively related to the densities of older fish, but not vice versa. These results support recent research on the sequence of regulation of salmonid populations, notably that density dependence can be manifested in growth rates at relatively low population densities (Achord et al 2003, Einum et al 2006, Lobón-Cerviá 2007 and that inter-cohort competition can occur in age-structured populations (Nordwall et al 2001, Kaspersson andHö jesjö 2009). Our results showed no conclusive effects of temperature on growth rates, either as a standalone factor or in interaction with age class density.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Growth rates in the subyearling age class were overall negatively related to the densities of older fish, but not vice versa. These results support recent research on the sequence of regulation of salmonid populations, notably that density dependence can be manifested in growth rates at relatively low population densities (Achord et al 2003, Einum et al 2006, Lobón-Cerviá 2007 and that inter-cohort competition can occur in age-structured populations (Nordwall et al 2001, Kaspersson andHö jesjö 2009). Our results showed no conclusive effects of temperature on growth rates, either as a standalone factor or in interaction with age class density.…”
Section: Discussionsupporting
confidence: 91%
“…Elliott (1985) found no evidence of competition between age classes of brown trout in England, whereas Nordwall et al (2001) reported on depressed growth in younger age classes with increased densities of older age classes in brown trout in Sweden. In two recent studies on brown trout in Sweden, Kaspersson and Hö jesjö (2009) found that the presence of yearling fish was associated with an overall reduction in subyearling growth rates, and Kaspersson et al (2013) reported on reduced growth rates, rather than increased mortality rates and movement, in small individuals when experimentally adding large brown trout to stream sections. Oppositely, Kvingedal and Einum (2011) found that subyearling brown trout densities in Norway were associated with depressed size-at-age for both subyearling and yearling fish, and that yearling density did not cause depressed sizes in either age class.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous experimental studies of inter-cohort interference suggest that the superior competitive ability of older cohorts can reduce both survival and growth rate of younger individuals (e.g. Crowley et al 1987;Nordwall et al 2001;Webster 2004;Kaspersson and Höjesjö 2009;Samhouri et al 2009). …”
Section: Introductionmentioning
confidence: 99%